IMPLEMENTASI MODEL GI-GI (GROUP INVESTIGATION-GUIDED INQUIRY) PADA PEMBELAJARAN MOMENTUM DAN IMPULS DI MAN - Aini Wardatut Thoyibah; Indrawati Indrawati; Alex Harijanto (JURNAL PEMBELAJARAN FISIKA, 2017)
The purposes of this research were to study the effect of the GI-GI (Group Investigation-Guided Inquiry) model to students' knowledge competence of momentum and impulse and to describe the students learning activities. The research was conducted at MAN 2 Jember Academic Year 2016 - 2017. The type of this research was experimental by Post-test Only Control Group Design. The population of the research were students of XI MIA in MAN 2 Jember. The sample was XI MIA 4 as an experimental class and XI MIA 2 as the control class. The researchs’ data which was collected by using documentation, observation, interview, and test. The techniques of data analysis used independent samples t-test and percentage (quantitative description). The results of this analysis were obtained significant value of 0.005 and the average activity of students was 71.39%. It can be concluded that GI-GI model had a significantly effect on students' knowledge competence of momentum and impulse and learning activities of students were in active category. Key words: Competence Knowledge, Learning Activities Model GI-GI, Momentum and impulse.